STRATEGI MILITER MODERN AZERBAIJAN DALAM PERANG NAGORNO-KARABAKH KEDUA TAHUN 2020 - Sasty, Elisya (Jurnal Studi Diplomasi dan Keamanan, 2026)
The Second Nagorno-Karabakh War of 2020 marked a significant change in the character of modern warfare, characterized by the dominance of information, the use of advanced technology, and the integration of cross-domain operations. This study aims to analyze how Azerbaijan applied modern military strategies in the conflict, emphasizing the interaction between technological innovation, doctrinal modernization, and operational effectiveness. Using a qualitative approach based on secondary data, this study examines the implementation of C4ISR systems, the use of UAVs and loitering munitions, and the execution of joint operations that formed the foundation of Azerbaijan's military success. The analysis is conducted through the Revolution in Military Affairs (RMA) framework as developed by Andrew W. Marshall and Andrew F. Krepinevich, which emphasizes the importance of integrating technology, doctrine, and organization in creating strategic superiority. Keywords : Armenia, Azerbaijan, Nagorno-Karabakh, Military Strategy